Layered Double Hydroxide/C (C=Humic Acid;Hydrochar) As Adsorbents of Cr(VI) - Patimah Mega Syah Bahar Nur Siregar; Alfan Wijaya; Amri; Juliana Putri Nduru; Nurlisa Hidayati; Aldes Lesbani; Risfidian Mohadi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
Layered double hydroxide (LDH) is known as a layered material that can be used as an adsorbent to remove pollutants from aqueous solutions. The use of layered double hydroxide as an adsorbent is not very effective due to its structure which is easily damaged so that it cannot be reused and its small surface area which results in a small adsorption capacity. This can be overcome by developing layered double hydroxide into a composite material. Modification of layered double hydroxide is done by using supporting materials in the form of humic acid and hydrochar. In this study the adsorbent was applied in the removal of Cr(VI) metal from aqueous solutions. The layered double hydroxide modification process was successfully carried out as seen from the XRD, FTIR, and BET analysis. XRD analysis shows the peaks that appear in Mg/Al-AH and Mg/Al-HC are peaks composed of their constituent materials, namely Mg/Al LDH, humic acid, and hydrochar. The vibrations that appear in Mg/Al-AH and Mg/Al-HC are vibrations originating from Mg/Al, humic acid, and hydrochar. The layered double hydroxide material composited with humic acid showed a surface area from 2.155 m2/g to 3.337 m2/g. The layered double hydroxide material composited with hydrochar showed a larger surface area than the Mg/Al LDH base material. The surface area increased 37 times, from 2.155 m2/g to 74.207 m2/g. The Mg/Al-AH composite showed the first adsorption ability of 89.064% and there was no significant decrease in the next cycle. The Mg/Al-HC composite showed adsorption ability in the first cycle which reached 97.079%, the ability to survive up to the fifth cycle with a final ability of 75.029%.